Synergistic Adsorption and Fluorescence in Porous Aromatic Frameworks for Highly Sensitive Detection of Radioactive Uranium - Suming Zhang; Siyu Wu; Cheng Zhang; Doudou Cao; Yingbo Song; Yue Zheng; Jiarui Cao; Lu Luo; Yajie Yang; Xiangjun Zheng; Ye Yuan (Molecules)
Uranium plays an important role in the modern nuclear industry. However, such a radioactive element can also cause severe damage to the environment once leaked or discharged into water or air, having a huge impact on the safety of the biosphere. In this work, we pioneered the use of fluorescent monomers as imprinted units, which promoted fluorescence emission of the material. A novel porous aromatic framework was obtained with uranyl ion chelating sites, namely MIPAF-15. The unique N-O chelating pockets on the 4-bromo-1-H-indole-7-carboxylic acid gave rise to high coordination affinity toward uranyl ions, which enabled the fast adsorption rate of uranyl ions and a uranyl ion adsorption capacity of 44.88 mg·g−1 at 298 K with an initial pH value of 6.0 and the uranyl concentration of 10 ppm. At the same time, the fluorescence quenching effect of MIPAF-15 was observed upon its adsorption of uranyl ions, which allowed the selective detection of uranyl ions with a detection limit of 5.04 × 10−8 M, lower than the maximum concentration of uranyl ions in drinking water specified by the World Health Organization (6.30 × 10−8 M) and United States Environmental Protection Agency (1.11 × 10−7 M). This kind of multifunctional porous material produces a favorable pathway for the detection, removal and degeneration of highly pollutive ions, promoting the overall sustainable development of the natural environment.